Treatment of anastomotic leakage after rectal cancer resection: The TENTACLE–Rectum study - van Workum, Frans (Colorectal Dis, 2020)
AIM: Anastomotic leakage is a severe complication after low anterior resection (LAR) for rectal cancer and occurs in up to 20% of patients. Most research focuses on reducing its incidence and finding predictive factors for anastomotic leakage. There are no robust data on severity and treatment strategies with associated outcomes. The aims of this work were (1) to investigate the factors that contribute to severity of anastomotic leakage and to compose an anastomotic leakage severity score and (2) to evaluate the effects of different treatment approaches on prespecified outcome parameters, stratified for severity score and other leakage characteristics. METHOD: TENTACLE–Rectum is an international multicentre retrospective cohort study. Patients with anastomotic leakage after LAR for primary rectal cancer between 1 January 2014 and 31 December 2018 will be included by each centre. We aim to include 1246 patients in this study. The primary outcome is 1‐year stoma‐free survival (i.e. patients alive at 1 year without a stoma). Secondary outcomes include number of reinterventions and unplanned readmissions within 1 year, total length of hospital stay, total time with a stoma, the type of stoma present at 1 year (defunctioning, permanent), complications related to secondary leakage and mortality. For aim (1) regression models will be used to create an anastomotic leakage severity score. For aim (2) the effectiveness of different treatment strategies for leakage will be tested after correction for severity score and leakage characteristics, in addition to other potential related confounders. CONCLUSION: TENTACLE–Rectum will be an important step towards drawing up evidence‐based recommendations and improving outcomes for patients who experience severe treatment‐related morbidity.